O uso de tecnologias digitais da informação e comunicação (TDIC) por docentes da educação básica de Boa Esperança do Sul - SP: reflexões sobre o antes, durante e depois da pandemia - Silva, Camila Fernanda Ferreira da (Universidade Federal de São Carlos, 2024)
Technology has been widely discussed due to its intense presence in contemporary society. With the COVID-19 pandemic that occurred between March 2020 and May 2023 and social isolation at the beginning of this period, technology had a global rise and entered even more different spaces, which needed to adapt to the new reality. It was no different in schools and thinking about technology in education, we must reflect on its use by teachers who had their practices rethought and reinvented so that classes during social isolation - Emergency Non-In-Person Teaching (ENPE) - could take place. Therefore, the theme of this research is the use of Digital Information and Communication Technologies –TDICs, by teachers, and our general objective is to identify the knowledge of teachers in the basic education network in the city of Boa Esperança do Sul - SP regarding TDICs and its use in pedagogical practices, in three different periods: before, during and after the COVID-19 pandemic. This research is of a mixed, quantitative and qualitative nature, and data collection occurred through the application of a questionnaire between the 11th and 12th of March, with open and closed questions relating to the theme of technology in education, which was answered by 120 teachers from the education department network and through a conference held on April 30th with 15 teachers from the network. Data analysis took place quantitatively with the data tabulated and described in tables and graphs and qualitatively following four thematic axes constructed based on the questions present in the questionnaire together with the theoretical contribution of the research and the objectives. Through the analyzes carried out, it was possible to identify that 56% of teachers did not undertake any type of course or training on the use of TDICs during the pandemic, however, 67% pointed out that despite the lack of training, the use of TDICs in their pedagogical practices increased after the pandemic, thus differentiating from pedagogical practices before the pandemic. We were also able to learn about the difficulties and needs of teachers in using TDICs, which is the lack of structure and continued training. We consider the theme of our research to be very relevant to science and we hope that with the results we can broaden reflections on teaching knowledge; pedagogical practices related to TDICs; teacher training; and subsidize the (re)elaboration of public policies.
The use of digital and comunication technologies (TDIC) by basic education teachers of Boa Esperança do Sul - SP: toughts about before, during and after the pandemics
Keywords: Políticas públicas; Tecnologias digitais; Formação de professores; Tecnologia na educação; Public policies; Digital technologies; Teacher training; Technology in education; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO